Sense and essence: heritage and the cultural production of the real - Meyer, Birgit; Port, Mattijs van de (Material Mediations: People and Things in a World of Movement, 2018)
Contrary to popular perceptions, cultural heritage is not given, but constantly in the making: a construction subject to dynamic processes of (re)inventing culture within particular social formations and bound to particular forms of mediation. Yet the appeal of cultural heritage often rests on its denial of being a fabrication, its promise to provide an essential ground to social-cultural identities. Taking this paradoxical feature as a point of departure, and anchoring the discussion to two heuristic concepts—the "politics of authentication" and "aesthetics of persuasion"—the chapters herein explore how this tension is central to the dynamics of heritage formation worldwide.